Evaluation of the SIF and T-stress values of the Brazilian disc with a central notch by hybrid method - Miarka, Petr; Sánchez-Cruces, Manuel Alejandro; Stanislav, Seitl; Malikova, Lucie; Lopez-Crespo, Pablo (Elsevier, 2020)
The near-crack-tip displacement field of a Brazilian disc with a central notch (BDCN) under mixed mode I/II conditions was measured via digital image correlation (DIC) and the stress intensity factor (SIF) was estimated using a hybrid method that allowed the fitting of the experimental data into the Williams series expansion. The effects of higher-order terms in the Williams expansion (T-stress) were analysed for different sizes of the crack tip fitting region and the results were compared with analytical predictions as well as with results obtained based on the numerically calculated crack-tip displacement field.
Keywords: Materiales - Fatiga; T-Stress; DIC; Brazilian disc; Concrete; Mixed mode I/II